Peranan Metode Dalam Meningkatkan Kualitas Pembelajaran Pada Anak Di TK Madinah Safitri - Mitta Pebri; Najwa Khairunnisa Panggabean; Nayla Nazwa Fauziah; Syahidah Awaliah Bintang; Wulan Hijriayani; Afrahul Fadhila Daulai (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The aim of this mini-research is to find out methods for improving the quality of learning at Madinah Safitri Kindergarten. This mini-research was carried out at Madinah Safitri Kindergarten Jl. Usman Siddik, Bandar Klippa, Kec. Percut Sei Tuan, Deli Serdang Regency, North Sumatra 20371. The research method uses qualitative methods. The data was obtained by directly observing the learning process at the Madinah Safitri Kindergarten. Insertion and model of learning strategies for play, child-centeredness and singing and prayer'.